Harold H. Burton papers - Burton, Harold H. (Harold Hitz), 1888-1964.
Correspondence, diaries (1941-1963), legal case files, speeches, writings, reports, broadsides, maps, newspaper clippings, printed matter, and photographs, chiefly relating to Burton's service as associate justice of the U.S. Supreme Court (1945-1958) and U.S. senator from Ohio (1941-1945). Subjects include his Cleveland law practice, Ohio and Republican Party politics, social life in Washington, D.C., Townsend Plan, Inc., the Truman Committee (U.S. Senate Special Committee Investigating the National Defense Program), U.S. Office of Price Administration, United Nations, Alaska, American Association of the Red Cross, American Unitarian Association, American Legion, Bowdoin College, and the U.S. Court of Appeals for the District of Columbia. Included in Burton's extensive Supreme Court files are bench and certiorari memoranda, conference lists, notes, drafts, opinions, docket books, and other files relating to such cases as Standard Oil v. Federal Trade Commission, Youngstown Sheet and Tube Company v. Sawyer, and Brown v. Board of Education. Also includes material on the Hitz family.
Correspondents include William J. Brennan, Owen Brewster, John W. Bricker, Styles Bridges, Harry Flood Byrd, Tom C. Clark, William O. Douglas, Felix Frankfurter, John M. Harlan, Earl E. Hart, William Hitz, J. Edgar Hoover, Robert Houghwout Jackson, Frank J. Lausche, Sherman Minton, Frank Murphy, Stanley Forman Reed, Donald R. Richberg, Harlan Fiske Stone, Robert A. Taft, Harry S. Truman, Fred M. Vinson, Henry Agard Wallace, and Charles Evans Whittaker.
Microfilm edition of diaries available, in part
Microfilm produced from originals in the Manuscript Division.
Library of Congress Prints and Photographs Division.
Lawyer, mayor of Cleveland, Ohio, U.S. senator from Ohio, and associate justice of the U.S. Supreme Court.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Brennan, William J. -- 1906-1997 -- Correspondence; Brewster, Owen, -- 1888-1961 -- Correspondence; Bricker, John W. -- 1893-1986 -- Correspondence; Bridges, Styles, -- 1898-1961 -- Correspondence; Brown, Oliver, -- 1918-1961 -- Trials, litigation, etc; Byrd, Harry F. -- 1887-1966 -- Correspondence; Clark, Tom C. -- 1899-1977 -- Correspondence; Douglas, William O. -- 1898-1980 -- Correspondence; Frankfurter, Felix, -- 1882-1965 -- Correspondence; Harlan, John M. -- 1899-1971 -- Correspondence; Hitz family; Hitz, William, -- 1872-1935 -- Correspondence; Hoover, J. Edgar -- 1895-1972 -- Correspondence; Jackson, Robert Houghwout, -- 1892-1954 -- Correspondence; Lausche, Frank John, -- 1895-1990 -- Correspondence; Minton, Sherman, -- 1890-1965 -- Correspondence; Murphy, Frank, -- 1890-1949 -- Correspondence; Reed, Stanley Forman, -- 1884-1980 -- Correspondence; Richberg, Donald R. -- 1881-1960 -- Correspondence; Sawyer, Charles, -- 1887- -- Trials, litigation, etc; Stone, Harlan Fiske, -- 1872-1946 -- Correspondence; Taft, Robert A. -- 1889-1953 -- Correspondence; Truman, Harry S., -- 1884-1972 -- Correspondence; Vinson, Fred M., -- 1890-1953 -- Correspondence; Wallace, Henry A. -- 1888-1965 -- Correspondence; Whittaker, Charles Evans, -- 1901-1973 -- Correspondence; American Association of the Red Cross; American Legion; American Unitarian Association; Bowdoin College; Republican Party (U.S. : 1854- ); Standard Oil Company -- Trials, litigation, etc; Topeka (Kan.). -- Board of Education -- Trials, litigation, etc; Townsend Plan, Inc; United Nations; United States. -- Congress. -- Senate; United States. -- Congress. -- Senate. -- Special Committee Investigating the National Defense Program; United States. -- Court of Appeals (District of Columbia Circuit); United States. -- Federal Trade Commission -- Trials, litigation, etc; United States. -- Office of Price Administration; United States. -- Supreme Court; Youngstown Sheet and Tube Company -- Trials, litigation, etc; Constitutional law -- United States; Law -- United States; Petroleum law and legislation -- United States -- Cases; Practice of law -- Ohio -- Cleveland; Segregation in education -- Law and legislation -- United States; Steel industry and trade -- Law and legislation -- United States; Alaska; Cleveland (Ohio) -- Politics and government; Ohio -- Politics and government -- 1865-1950.; Washington (D.C.) -- Social life and customs; Hart, Earl E. -- Correspondence; Jurists; Lawyers; Mayors -- Ohio -- Cleveland; Senators, U.S. Congress -- Ohio